STRENGTHENING ISLAMIC BANKING SERVICES IN INDONESIA THROUGH BLOCKCHAIN TECHNOLOGY: THE ANP- STEP APPROACH - Rahmayati Rahmayati (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2021)
The purpose of this research is to examine so that financial services in Islamic banking are strong through digitization of blockchain applications that provide benefits to Islamic financial technology (fintech), through aspects of Security, Transparency, Efficiency, Permanent (STEP). The research data were obtained from in-depth interviews and then completed questionnaires from respondents who had been determined by using purposive sampling technique. The data analysis of this study used the Analytical Network Process (ANP) method with Super Decision software through the STEP aspect. The results show that the blockchain technology adopted by Islamic banking in Indonesia can strengthen financial services by using the STEP aspect, which is an integral part of facilitating the process, access, and proving the role of blockchain in Islamic banking business products.